Contractile function and motor unit firing rates of the human hamstrings - Kirk, Eric A. (J Neurophysiol, 2016)
Neuromuscular properties of the lower limb in health, aging, and disease are well described for major lower limb muscles comprising the quadriceps, triceps surae, and dorsiflexors, with the notable exception of the posterior thigh (hamstrings). The purpose of this study was to further characterize major muscles of the lower limb by comprehensively exploring contractile properties in relation to spinal motor neuron output expressed as motor unit firing rates (MUFRs) in the hamstrings of 11 (26.5 ± 3.8) young men. Maximal isometric voluntary contraction (MVC), voluntary activation, stimulated contractile properties including a force-frequency relationship, and MUFRs from submaximal to maximal voluntary contractile intensities were assessed in the hamstrings. Strength and MUFRs were assessed at two presumably different muscle lengths by varying the knee joint angles (90° and 160°). Knee flexion MVCs were 60–70% greater in the extended position (160°). The frequency required to elicit 50% of maximum tetanic torque was 16–17 Hz. Mean MUFRs at 25–50% MVC were 9–31% less in the biceps femoris compared with the semimembranosus-semitendinosus group. Knee joint angle (muscle length) influenced MUFRs such that mean MUFRs were greater in the shortened (90°) position at 50% and 100% MVC. Compared with previous reports, mean maximal MUFRs in the hamstrings are greater than those in the quadriceps and triceps surae and somewhat less than those in the tibialis anterior. Mean maximal MUFRs in the hamstrings are influenced by changes in knee joint angle, with lower firing rates in the biceps femoris compared with the semimembranosus-semitendinosus muscle group. NEW & NOTEWORTHY We studied motor unit firing rates (MUFRs) at various voluntary contraction intensities in the hamstrings, one of the only major lower limb muscles to have MUFRs affected by muscle length changes. Within the hamstrings muscle-specific differences have greater impact on MUFRs than length changes, with the biceps femoris having reduced neural drive compared with the semimembranosus-semimembranosus. Comparing our results to other lower limb muscles, flexors have inherently higher firing rate compared with extensors.